2021
DOI: 10.1159/000515231
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcomes of Acute Kidney Diseases: A Comparative Analysis

Abstract: <b><i>Introduction:</i></b> Acute kidney diseases and disorders (AKD) encompass acute kidney injury (AKI) and subacute or persistent alterations in kidney function that occur after an initiating event. Unlike AKI, accurate estimates of the incidence and prognosis of AKD are not available and its clinical significance is uncertain. <b><i>Methods:</i></b> We studied the epidemiology and long-term outcome of AKD (as defined by the KDIGO criteria), with or without AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“… 38 According to previous studies, the incidence of AKD in patients without an identified AKI episode is 17% to 37.8%. 39 , 40 , 41 , 42 Our study revealed that approximately 40% and 20% of patients with AKI and patients without AKI developed AKD after ADHF, respectively.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“… 38 According to previous studies, the incidence of AKD in patients without an identified AKI episode is 17% to 37.8%. 39 , 40 , 41 , 42 Our study revealed that approximately 40% and 20% of patients with AKI and patients without AKI developed AKD after ADHF, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…Both AKI and AKI severity are associated with AKD development 38 . According to previous studies, the incidence of AKD in patients without an identified AKI episode is 17%-37.8% [39][40][41][42] . Our study showed that approximately 40% and 20% of AKI patients and non-AKI patients developed AKD after ADHF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a comparison of the primary composite outcomes of incident CKD, kidney failure, or death between hospitalized patients with AKD without AKI and patients with AKD post-AKI, the latter defined by the ADQI definition, was recently published [95]. Compared with no AKD, both groups with AKD showed similar hazard ratios for the primary outcomes.…”
Section: The Concept Of Akd and Its Interrelationship With Aki And Ckdmentioning
confidence: 99%
“…A large population-based observational study discovered a statistically significant association between AKD and major adverse kidney events (MAKEs) related to CKD progression, ESKD, and mortality 10 . With or without AKI, AKD was also found to be associated with adverse clinical outcome among hospitalized patients 11 .…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, the disparate definitions of AKD might indicate variance in the acuity and severity of kidney disease among different subgroups of AKD patients 12 . Persistent kidney dysfunction for more than 7 days after AKI (post-AKI AKD) is associated with adverse renal and cardiovascular outcomes 11 , 13 17 . The 16th Acute Disease Quality Initiative (ADQI) recommends definitions and staging criteria for post-AKI AKD and renal recovery, but the clinical trajectories of renal function after AKI and the prognostic value of AKD staging remain largely unknown 2 , 18 .…”
Section: Introductionmentioning
confidence: 99%